The Relevance of Endeavors to God's Destiny (Analytical Study of Q.S. An-Najm Verses 39-42 in the Interpretation of Nurul Qur'an) - Rizal Ramdani; Pathur Rahman; Deddy Ilyas (Tilawah: Journal of Al-Qur'an Studies, 2026)
This research is entitled "The Relevance of Efforts to Allah's Destiny (Analytical Study of Q.S. An-Najm Verses 39-42)". Effort is an effort made by humans to achieve something desired, while destiny is something that has been determined by Allah and revealed to His creatures on earth. Effort and destiny are closely related. When humans have made every effort, they must be patient to accept the results of their destiny. This study seeks to uncover the meaning of effort and Allah's destiny (Analytical Study of Q.S. An-Najm Verses 39-42), from the interpretation of Ayatullah Allamah Kamal Faqih Imani. Specifically, this paper begins with two questions: the meaning of effort and destiny in the interpretation of Nurul Qur'an and the relevance of effort and destiny for humans. The discussion of the two issues above will be described using the tahlili interpretation method, which defines all aspects of the Quran's content comprehensively, explains them according to their sequence in the Quran, explains each verse individually with a global and detailed explanation, and then includes correlations within the verses and explains the relationship between them. This was done to ensure a more focused research. This study used a library research method that collected literature sources relevant to the research. The conclusions of this study are: 1) endeavor and destiny have a strong relevance. Human endeavor is a means to achieve hopes and aspirations. However, Allah has determined destiny for human endeavor, so after endeavoring, humans must submit everything they have done to Allah. 2) In implementing endeavor and destiny, according to Ayatollah Kamal Faqih Imani's understanding in his interpretation of the Nurul Qur'an, humans must always strive earnestly to achieve their hopes and dreams. In line with destiny, humans are obliged to return all their efforts to Allah.